Composition and importance value of tree-families in undisturbed and disturbed moist tropical forest of eastern Nepal - Gautam, Tilak Prasad; Mandal, Tej Narayan (Nepalese Journal of Biosciences, 2017)
Tropical forest disturbances have reduced the tree species diversity and hereby, the ecosystem services provided by them. Present study was carried out to understand the status of tree-families in terms of their dominance in the undisturbed and disturbed stands of moist tropical forest in eastern Nepal. As per the result, the dominant family in both the forest was Dipterocarpaceae, with family importance value of 53.6 and 53.9 in undisturbed and disturbed stands, respectively. The second dominant family in both forest stands was Rubiaceae.